Influence of Femoral Component Flexion on Outcomes After Primary Total Knee Arthroplasty - Praharsha Mulpur, MBBS, DNB (Ortho); Tarun Jayakumar, MBBS, MS (Ortho); Mudidana Prudhvi, MBBS, MS (Ortho); Krishna Raj Khanal, MBBS, MS (Ortho); Kushal Hippalgaonkar, MBBS, DNB (Ortho); A.V. Gurava Reddy, MBBS, D.Ortho, DNB (Ortho), FRCS, MCh (Ortho) (Arthroplasty Today, 2025)
Background: Total knee arthroplasty (TKA) improves pain relief and function in end-stage arthritis. While coronal alignment has been well studied, the impact of femoral component flexion in the sagittal plane on outcomes remains underexplored. This study examines the effect of femoral component flexion on patellofemoral outcomes, using the Kujala anterior knee pain scale, and overall functional results after robotic-assisted TKA. Methods: A retrospective review was conducted on 285 patients who underwent primary robotic-assisted TKA between January 2022 and January 2023. Femoral component flexion was classified as low (0°-2.5°), medium (2.6°-5.5°), and high (5.6°-8°). Outcomes were assessed preoperatively and 12 months postoperatively using the Kujala score, Oxford Knee Score (OKS), and Knee Society Score (KSS). Statistical analysis included analysis of variance for comparing groups and regression analysis to evaluate the impact of flexion on outcomes. Results: A total of 57, 108, and 120 patients were categorized into low, medium, and high flexion groups, respectively. Kujala scores were significantly higher in the low flexion group (73.89 ± 12.68) compared to medium (63.08 ± 7.07) and high groups (63.12 ± 6.86, P < .0001). Each additional degree of femoral flexion resulted in a 1.34-point decrease in Kujala score (P < .0001). Postoperatively, the OKS and KSS improved significantly in all groups, with no statistically significant difference across flexion groups. Patient satisfaction was comparable across groups, with no significant difference. Conclusions: Increased femoral component flexion was associated with poorer patellofemoral outcomes based on the Kujala score. However, the overall patient-reported functional outcome, as measured by the OKS and KSS, did not show a correlation with the flexion of the femoral component.